2018
DOI: 10.3390/app8081258
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Phase-Only Holograms with JPEG Standard and Deep Learning

Abstract: It is a critical issue to reduce the enormous amount of data in the processing, storage and transmission of a hologram in digital format. In photograph compression, the JPEG standard is commonly supported by almost every system and device. It will be favorable if JPEG standard is applicable to hologram compression, with advantages of universal compatibility. However, the reconstructed image from a JPEG compressed hologram suffers from severe quality degradation since some high frequency features in the hologra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In recent years, deep learning receives much attention in many research fields including optical design [1,2] and optical imaging [3]. In previous works, deep learning has been extensively applied for many optical imaging problems including phase retrieval [4][5][6][7], microscopic image enhancement [8][9], scattering imaging [10][11], holography [12][13][14][15][16][17][18], single-pixel imaging [19,20], super-resolution [21][22][23][24], Fourier ptychography [25][26][27], optical interferometry [28,29], wavefront sensing [30,31], and optical fiber communications [32].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep learning receives much attention in many research fields including optical design [1,2] and optical imaging [3]. In previous works, deep learning has been extensively applied for many optical imaging problems including phase retrieval [4][5][6][7], microscopic image enhancement [8][9], scattering imaging [10][11], holography [12][13][14][15][16][17][18], single-pixel imaging [19,20], super-resolution [21][22][23][24], Fourier ptychography [25][26][27], optical interferometry [28,29], wavefront sensing [30,31], and optical fiber communications [32].…”
Section: Introductionmentioning
confidence: 99%
“…In this deep learning approach, the author proposed a noniterative method using ResNet to generated the holograms and then compared it with the iterative method (Gerchberg-Saxton). In [15], to the best of our knowledge, the authors presented a method to employ deep neural networks to reduce losses in a JPEG compressed hologram, as the reconstructed image of JPEG compressed hologram suffers from extreme quality loss because, during the compression process, certain high-frequency features in the hologram will be lost. e proposed framework in [16] is called deep learning invariant hologram classification (DL-IHC) and the authors introduced a self-attention to convolution neural network (CNN) to implement a classification hologram of deformable objects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The deep neural networks can solve many remaining problems in fields of scattering imaging, computational ghost imaging, Fourier laminar microscopic imaging, phase retrieval and hologram data compression etc. [5][6][7][8][9][10][11]. It is shown that as an object passes through a scattering medium or multimode fiber (MMF), the information of the image is deteriorated.…”
Section: Introductionmentioning
confidence: 99%